The New Evolutionary Trajectory of University Libraries: The Editor-in-Chief’s View - KOLESNYKOVA, T. O. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2022)
The paper provides a brief overview of the events/issues that the authors of the 7(2022) issue of the UniLibNSD journal cover in their articles. The authors’ many issues are highlighted through evidence of the nature of these challenges, as well as theoretical and concrete examples of how to address them. At a time of tectonic shifts in global geopolitics, climate change, digital development, the fight against the COVID 2019 pandemic, social transformations, librarians have witnessed russia’s full-scale aggression against Ukraine and against world democracy, including the terrible destruction of Ukrainian libraries and archives by russian terrorists who continue their fierce offensive against the world’s documentary heritage. That is why most of the authors challenge traditional concepts of librarianship, argue that libraries are not neutral, and call on the world’s librarians to take active measures to prevent genocide, anti-racist and anti-oppressive practices for the benefit of both users and the profession itself.